Membangun Komunitas Belajar Profesional Guru Melalui Supervisi Akademik Partisipatif oleh Kepala Sekolah Transformasional - Kusumawati, Erna (Jayapangus Press, 2024)
This study examines the role of transformational principals in building teacher Professional Learning Communities (PLCs) through participatory academic supervision. The background of this study is the urgency of improving teacher professionalism as the key to educational quality, but the integration between transformational leadership and participatory supervision in the formation of PCLs is still less elaborated in the literature. The purpose of this study is to analyze the role of transformational principals in facilitating PCLs, identify effective participatory supervision strategies that are implemented, and explore their impact on improving teacher professionalism. This study uses a qualitative multi-site case study method, allowing for in-depth data mining and cross-context comparisons. Data were collected through interviews, observations, and documentation, then analyzed thematically to identify patterns and meanings. The results show that transformational principals play a crucial role as inspirators and facilitators, actively implementing collaborative supervision strategies that effectively encourage the formation and strengthening of PCLs. This implementation resulted in significant improvements in collaboration between teachers, pedagogical capacity, intrinsic motivation, and teacher reflection culture. The conclusion of this study is that the principal's transformational leadership, combined with participatory academic supervision, is a very effective strategy for building and strengthening teacher KBP, which in turn directly improves teacher professionalism. This study provides valuable contributions to school leadership practices and teacher professional development policy formulation, confirming participatory supervision as an effective strategy for continuously improving the quality of education.